IMPLEMENTASI KEBIJAKAN PENGADAAN ALUTSISTA UNTUK MENDUKUNG KEBUTUHAN OPERASIONAL TENTARA NASIONAL INDONESIA (Studi Kasus Pengadaan Alutsista Renstra 2005-2009) - , Agus Sudarmanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research was conducted to determine how the organization and procurement mechanisms Weapon Systems last 15 years, the factors that influence the implementation of procurement policies, and strategies used to achieve the successful implementation of the policy. This research was conducted with qualitative methods, giving priority to data collection, data analysis (literature study), and indepth interviews with the involved process of budget planning, implementation, procurement, financing and procurement. This study shows that: (1) Weapon Systems procurement mechanism is the implementation of policies on procurement, which is implemented in a unique and special because of the complex material properties, in the last 15 years has carried out Weapon Systems procurement reform, (2) Implementation of policies is not merely application of regulations, but should be able to increase competence in completing the work load, its practice is influenced by several factors: regulations